2002
DOI: 10.1016/s0028-3932(02)00017-9
|View full text |Cite
|
Sign up to set email alerts
|

Haptic study of three-dimensional objects activates extrastriate visual areas

Abstract: In humans and many other primates, the visual system plays the major role in object recognition. But objects can also be recognized through haptic exploration, which uses our sense of touch. Nonetheless, it has been argued that the haptic system makes use of 'visual' processing to construct a representation of the object. To investigate possible interactions between the visual and haptic systems, we used functional magnetic resonance imaging to measure the effects of cross-modal haptic-to-visual priming on bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
267
4
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(308 citation statements)
references
References 27 publications
35
267
4
2
Order By: Relevance
“…(5A-C)). The region is similar to the location (similar Talairach coordinates) found in previous object processing tasks focusing on shape, the lateral occipital complex [35][36][37][38]. One possible explanation for the current result is that although shape processing is a component of both object inspection and mental rotation, the mental rotation condition relies more on shape information.…”
Section: Occipital/temporal Cortexsupporting
confidence: 84%
“…(5A-C)). The region is similar to the location (similar Talairach coordinates) found in previous object processing tasks focusing on shape, the lateral occipital complex [35][36][37][38]. One possible explanation for the current result is that although shape processing is a component of both object inspection and mental rotation, the mental rotation condition relies more on shape information.…”
Section: Occipital/temporal Cortexsupporting
confidence: 84%
“…Consistent with this suggestion, studies have demonstrated that the visual cortex of blind individuals is activated during tasks such as Braille reading (Cohen et al, 1997;Sadato et al, 1996) and haptic object recognition (Amedi, Raz, Azulay, Malach, & Zohary, 2010). Moreover, the existence of networks between vision and touch in normally sighted individuals is supported by neuroimaging studies; visual areas have been shown to be activated during tactile orientation discrimination (Sathian & Zangaladze, 2002;Sathian, Zangaladze, Epstein, & Grafton, 1999), haptic object recognition (Amedi, Jacobson, Hendler, Malach, & Zohary, 2002;Amedi et al, 2010;Deibert, Kraut, Kremen, & Hart, 1999;James, Humphrey, Gati, Servos, Menon, & Goodale, 2002;Pietrini et al, 2004), and Braille reading in sighted subjects following 5 days of complete visual deprivation (Merabet et al, 2008). Furthermore, there is behavioral evidence for the influence of tactile inputs on visual perception.…”
Section: Introductionmentioning
confidence: 68%
“…In subsequent experiments, we will also allow participants to actively manipulate the objects such that they can analyze and compare them from all viewpoints. In addition, we are planning neuro-imaging experiments using fMRI which would allow us to show if visual and haptic exploration of the shell-shaped objects would activate the same brain areas and thus if the underlying map is processed by similar brain structures for both modalities [12]. Additionally, any differences in activating these brain structures could be correlated to modality.…”
Section: Discussionmentioning
confidence: 99%